Linking sustainable livelihoods to natural resources and governance in OIC countries: prospects and challenges - Abdulai, Abdul-Mumin; Siwar, Chamhuri (The Statistical, Economic and Social Research and Training Centre for Islamic Countries (SESRIC), 2011)
This article investigates natural resource endowment and good governance, and the extent to which these two variables impact sustainable livelihoods in the Organisation of Islamic Conference (OIC) member countries. This study draws heavily from secondary data. The findings revealed that countries having better scores in good governance performed better in more than one of the selected livelihood indicators. Performances in the selected indicators for sustainable livelihoods and good governance vary markedly among the countries, which underscores the need to intensify the existing collaboration. The study has proposed a collaboration model that is all-inclusive seeking to enhance development collaboration among the OIC countries.